Godzilla mineral dust and La Soufrière volcanic ash fallout immediately stimulate marine microbial phosphate uptake - Hope Elizabeth Elliott; Kimberly J. Popendorf; Edmund Blades; Haley M. Royer; Clément G. L. Pollier; Amanda M. Oehlert; Ravi Kukkadapu; Andrew Ault; Cassandra J. Gaston (Frontiers in Marine Science, 2024)
During the “Godzilla” dust storm of June 2020, unusually high fluxes of mineral dust traveled across the Atlantic from the Sahara Desert, reaching the Caribbean Basin, Gulf Coast, and southeastern United States. Additionally, an eruption of the La Soufrière volcano on St. Vincent in April 2021 generated substantial ashfall in the southeastern Caribbean. While many studies have analyzed mineral dust’s ability to relieve nutrient limitation of phosphorus (P) in the P-stressed North Atlantic, less is known about the impact of extreme events and other natural aerosols on fluxes of P into seawater and from seawater into marine microbial cells. We quantified P and iron (Fe) content in mineral dust from the Godzilla dust storm and volcanic ash from the La Soufrière eruption collected at Ragged Point, Barbados. We also performed seawater incubations to assess the marine microbial response to aerosol deposition. Using environmentally-relevant concentrations of atmospheric particles for within the ocean’s mixed layer allowed us to draw realistic conclusions about how these deposition events impacted P cycling in situ. Volcanic ash has lower P content than mineral dust, and P in volcanic ash is far less soluble (~1%) than assumed in current atmospheric deposition models. Adding mineral dust and the volcanic ash leachate in concentrations representing different deposition scenarios increased soluble reactive phosphorus (SRP) concentrations in coastal seawater by ~7-32 nM. Phosphate uptake rate was stimulated in coastal seawater after either mineral dust or volcanic ash deposition at aerosol concentrations relevant to the Godzilla dust event, with ash eliciting the fastest uptake rate. Furthermore, high concentrations of both the mineral dust and volcanic ash led to slightly elevated alkaline phosphatase activity (APA) compared to the relevant controls, indicating higher potential for use of dissolved organic phosphorus (DOP) as a P source. Quantifying these aerosols’ impacts on P cycling is a significant step towards achieving a better understanding of their potential roles in relieving nutrient limitation and fueling the biological carbon pump.